Synthesis, characterization, antibacterial activities and molecular docking studies of some novel therapeutic N, N’- disubstituted β-branched Nitroolefin Piperazine derivatives - J. IRSHAD AHAMED; K. S. MEENA (International Journal of Pharma and Bio Sciences, 2018)
Piperazines are a wide class of chemical compounds with numerous important pharmacological properties. An ease and highly efficient synthetic protocol was accomplished for the synthesis of novel N, N’-disubstituted β-branched nitroolefin containing new piperazine molecular architectures. As the Michael addition of alkyl anion equivalents to simple nitro olefins proceeds in a non-stereo selective way, the lofty stereo selectivity requires heteroatom substituent on the β - position of the nitronated anion intermediates. Eleven new N,N’-disubstituted β-branched nitroolefin piperazine derivatives were synthesized using this technique, purity of compounds was ascertained by melting point and thin-layer chromatography. All Compounds have been characterized by 1H – 13C NMR. Among the synthesized new compound 10g 1,4-bis((E)-3-(3,4-dimethoxyphenyl)-2-nitroallyl)piperazine exhibited potent antimicrobial activities by both Disc diffusion and broth dilution method. The synthesized compounds were subjected to molecular docking studies through commercial software using Discovery Studio 4.0. Furtherly the pharmacokinetics properties were studied by ADMET (Absorption, Distribution, Metabolism, Excretion, Toxicity). DMol3 Properties and B3LYP functions were executed in DFT (Density Functional Theory studies) DS 4.0. The compound 10g was found to be a potent and safe by ADMET studies. The compound10g could be proposed for further in vitro and in vivo studies.